تأثير وسيلة ثلاثية الأبعاد في ترقية استيعاب المفردات لدى طلاب الفصل الرابع في المدرسة الابتدائية الإسلامية جاحايا هاتي بوكيت تنجي - Wulandari, Afrila; Husni, Arman; Dewi, Yelfi; Rizal, Eka (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Afrila Wilandari (2217001) The Influence of Three-Dimensional (3D) Media towards The Enhancement of Students’ Vocabulary Comprehension at The Fourth Grade of Cahaya Hati Elementary Islamic School of Bukittinggi. The problem of study in this research was there were a lot of students that know much English vocabularies but lack of comprehension in it. Therefore, in order to enhance the students’ vocabulary comprehension, an effective teaching aid is needed to help the students improve their vocabulary comprehension. The objective of this research was to determine whether the three-dimensional (3D) media as a teaching aid is influential towards the enhancement of students’ vocabulary comprehension at the fourth grade of Cahaya Hati Elementary Islamic School of Bukittinggi. The researcher used an expert validation test in order to correct the data. Before analyse data, the researcher conducted a normality and homogeneity test using SPSS with Kolmogrov-Simirnov formula and one-way ANOVA test, continued by examined the hypothesis using one sample t-test. The result showed that vocabulary teaching to students before using this 3D media method was get a score of 76,06. While the result after using this 3D media method showed that the mean score of post-test score in experimental class was 84,03. Therefore, the acceptance of H0 was rejected. Based on the table of “paired sample t-test”, the researcher found that sig (2-tailed) equal to 0,00 which was higher than 0,005. Thus, it can be concluded that using of three-dimensional (3D) media is effective in teaching vocabulary and be able to enhance the result of students’ vocabulary comprehension at the fourth grade of Cahaya Hati Elementary Islamic School of Bukittinggi